1986
DOI: 10.1128/jb.168.3.1439-1443.1986
|View full text |Cite
|
Sign up to set email alerts
|

Malate transport in Schizosaccharomyces pombe

Abstract: The transport of malate was studied in a Schizosaccharomyces pombe wild-type strain and in mutant strains unable to utilize malic acid. Two groups of such mutants, i.e., malic enzyme-deficient and malate transportdefective mutants, were differentiated by a '4C-labeled L-malate transport assay and by starch gel electrophoresis followed by activity staining for malic enzyme (malate dehydrogenase [oxaloacetate decarboxylating] [NAD+]; 1.1.1.38) and malate dehydrogenase (1.1.1.37). Transport of malate in S. pom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…It has been suggested that the S. pombe L-malic acid transporter is a carboxylate/proton symport system, dependent on the plasma membrane proton gradient (22). The MAE1 gene, encoding the permease for L-malic acid and other organic acids, has been cloned (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that the S. pombe L-malic acid transporter is a carboxylate/proton symport system, dependent on the plasma membrane proton gradient (22). The MAE1 gene, encoding the permease for L-malic acid and other organic acids, has been cloned (18).…”
Section: Discussionmentioning
confidence: 99%
“…The transport systems involved are inducible and subject to glucose repression. In contrast, it has been suggested that the uptake of L-malic acid is mediated by a protein and occurs in the presence of glucose in Zygosaccharomyces bailii (3) and in Schizosaccharomyces pombe (22). The heter-ologous expression of a gene encoding such an L-malic acid permease appeared to be a possible way of improving malate uptake in S. cerevisiae during alcoholic fermentation.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Uptake of dicarboxylic acids in yeasts has been reported in several papers (4,9,11,12,26,28,32). It is believed that several yeast strains, such as Schizosaccharomyces pombe, Candida sphaerica, Candida utilis, and Hansenula anomala, can import dicarboxylic acids via a proton symport mechanism.…”
mentioning
confidence: 99%
“…Cells of S. pombe are not able to utilize malate as the sole energy source or incorporate the malate into biomass (2) and therefore require glucose or other carbon sources for the energy-dependent transport and efficient degradation of malic acid (3). Three enzymes are involved in malate degradation in S. pombe, namely the malate transporter, malic enzyme, and malate dehydrogenase (4). The transporter, encoded by the mae1 gene (5), uses an H ϩ -symport system for the active transport of L-malate, and the NAD-dependent malic enzyme (EC 1.1.1.38) catalyzes the oxidative decarboxylation of L-malate to pyruvate and CO 2 .…”
mentioning
confidence: 99%